27 Impact of multivessel disease on clinical endpoints. (28th September 2016) - Abdullah, A; Ahmed, M; Cahill, C; Ahern, C; Mannix, K; Meany, B; Hennessy, T; Arnous, S; Keary, L; Keane, M; Kiernan, T
Abstract : Introduction: There is a large subset of patients with ST elevation myocardial infarction (STEMI) with significant disease beside the culprit artery. Multivessel disease has been reported as one of the predictors of worse outcome. It is not clear if this related to incomplete revascularisation or due to increased disease burden per se. Purpose and methods: In this study we retrospectively reviewed 317 patients who were admitted with STEMI in our centre to estimate the effect of multivessel disease on clinical outcomes in terms of mortality, heart failure and length of stay. We tested whether incomplete revascularisation impacts MVD as predictor of clinical outcomes. A retrospective review of 317 patients who attended our centre between January 2013 to December 2014. Medical records and angiographic reports were reviewed. Patients were divided into two groups, MVD group V's single artery group. Mortality rates between the two groups were compared using X 2 test and binary logistic regression estimate Odd ratio using STAT14.0. Results: Of 317 patients who presented with STEMI, 95.3% received PPCI with the remaining unsuitable for coronary angiography for various reasons. The mean age of patients was 65 years. 27.13% were female. In hospital mortality was 8.2% and 1 year mortality = 10.74% (P = 0.35). 58.5% had two-vessel disease or more (33.7% two, 22.8% three-vessel disease, 2% 4-vessel disease). Multivessel disease was associated with increased in-hospital mortality of 9.44% vs 3.15% up to 12.35% vs 5.0% 1-year mortality (P = 0.031, 0.034) Odd ratio = 3.2. Patients with multivessel disease tend to be older (mean 66.8 vs 61) and have longer hospital stay (mean = 5.6 vs 3.9 days). Female sex, ejection fraction, symptomatic heart failure, use of Intra-aortic balloon pump were similar between the two groups. Repeat revascularisation, myocardial infarction, repeat angiogram for chest pain and readmission rates were similar between the two groups. With multivariae logistric regression, only age was independent predictor of mortality in this cohort. Conclusion: MVD in patients with STEMI is associated with higher mortality and longer hospital stay. The increased mortality can be attributed to older age in patients with MVD and incomplete revascularisation.